2021
DOI: 10.3390/v13020218
|View full text |Cite
|
Sign up to set email alerts
|

Alternative mRNA Processing of Innate Response Pathways in Respiratory Syncytial Virus (RSV) Infection

Abstract: The innate immune response (IIR) involves rapid genomic expression of protective interferons (IFNs) and inflammatory cytokines triggered by intracellular viral replication. Although the transcriptional control of the innate pathway is known in substantial detail, little is understood about the complexity of alternative splicing (AS) and alternative polyadenylation (APA) of mRNAs underlying the cellular IIR. In this study, we applied single-molecule, real-time (SMRT) sequencing with mRNA quantitation using shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…RSV replicates in primary human airway epithelial cells, inducing a well-established, time-dependent global genomic response, including both gene activation and repression ( Zhang et al, 2001 ; Xu et al, 2020 ; Xu et al, 2021a ). Consistent with this earlier study, our data indicate that RSV induces dramatic changes in the expression of 11,038 genes (5620 upregulated and 5418 downregulated).…”
Section: Resultsmentioning
confidence: 99%
“…RSV replicates in primary human airway epithelial cells, inducing a well-established, time-dependent global genomic response, including both gene activation and repression ( Zhang et al, 2001 ; Xu et al, 2020 ; Xu et al, 2021a ). Consistent with this earlier study, our data indicate that RSV induces dramatic changes in the expression of 11,038 genes (5620 upregulated and 5418 downregulated).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that antiviral pathways and interferon pathways play important roles in COVID-19 patients (38)(39)(40)(41), but the exact mechanism remained unclear. Simultaneously, previous studies have found that APA and AS regulated multiple viral immune processes (7,8,13,(42)(43)(44). However, there is a lack of studies on whether APA affects SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the IRF7 protein level is reduced to facilitate viral replication [ 28 ]. Several other IRF7 transcript variants have been reported, and some may be induced by respiratory syncytial virus (RSV) infection [ 29 , 30 ].…”
Section: Alternative Rna Splicing and Its Isoforms In Type I And Iii Ifn Responsesmentioning
confidence: 99%